Law Enforcement against Sexual Violence Crimes at the Pangkalpinang Police Resort in 2024 - Alifah Oktavirgianti; M. Ilham Wira Pratama (SIGn Jurnal Hukum, 2026)
Sexual violence constitutes a violation of human rights that requires the implementation of legal instruments to ensure victim protection and recovery. This study aims to examine and analyze victim protection-based law enforcement against sexual violence crimes under Law Number 12 of 2022 at Pangkalpinang Police Resort in 2024, and to identify empirical factors that hinder the effectiveness of investigations. This normative-empirical legal research uses a statutory approach with qualitative analysis. Primary data were obtained through in-depth interviews and limited field observations and analyzed using descriptive qualitative analysis. The findings show that the police have implemented victim protection mechanisms through victim-centered examination, separation of the examination room, psychological assistance, and an understanding of the expanded scope of evidence. However, the effectiveness of investigation remains limited by the insufficient number of trained investigators, the unmet adequacy standards of the special service room for victims, and barriers to interagency coordination. Externally, social stigma, pressure arising from power relations, and victims’ reluctance to report demonstrate obstacles at the pre-reporting stage and affect initial medical and forensic examinations. This study recommends strengthening investigator capacity, improving the standards of special service rooms for victims, establishing integrated operating procedures with health institutions and victim support providers, and developing human rights-based legal literacy in the community.